2018
DOI: 10.5812/jhealthscope.65330
|View full text |Cite
|
Sign up to set email alerts
|

Presenting a Model for Periodontal Disease Diagnosis Using Two Artificial Neural Network Algorithms

Abstract: Background: Artificial neural networks (ANNs) can be used in various medical cases due to their high performance in learning the relationship between variables. Periodontal diseases are common oral infectious diseases that can cause tooth loss, if not treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…They divided 190 patients into two groups (n = 160 for train) and (n = 30 for test) and studied them by examining age, sex, plaque index, probing pocket depth, and clinical attachment loss index as an input variables. Two Levenberg-Marquardet (LM) and Scaled Conjugate Gradient (SCG) algorithms have been used in this work, results showed that a better performance for the LM than SCG [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They divided 190 patients into two groups (n = 160 for train) and (n = 30 for test) and studied them by examining age, sex, plaque index, probing pocket depth, and clinical attachment loss index as an input variables. Two Levenberg-Marquardet (LM) and Scaled Conjugate Gradient (SCG) algorithms have been used in this work, results showed that a better performance for the LM than SCG [23].…”
Section: Discussionmentioning
confidence: 99%
“…In this cross-sectional study, the records of 300 patients referred to the Periodontics department of Hamadan University of Medical Sciences, west of Iran, between September 2016 and June 2018 were studied. Based on consultation with two experienced professionals of periodontology as well as a review of clinical studies, the desired variables were selected [14,15,21,23]. The corresponding values of the selected variables were extracted and recorded for each patient with full confidentiality principles.…”
Section: Methodsmentioning
confidence: 99%
“…Papantonopoulos et al [136] establish an Ann's modal to distinguish AgP from ChP based on monocytes, eosinophils, neutrophils, and CD4 / CD8 ratio. Arbabi et al [137] established a diagnosis tool based on ANNs, which can accurately diagnose periodontal disease by evaluating age, sex, probing depth, plaque index, and attachment loss index.…”
Section: ) Diagnose Periodontitismentioning
confidence: 99%
“…LM method has achieved better performance than SCG. [27]The same methodology can be implemented in future with extended and added inputs apart from considered in this paper for more accurate results.…”
Section: Literature Surveymentioning
confidence: 99%